Isolation and characterization of the complete mitochondrial genome of Taenioides anguillaris (Gobiidae: Amblyopinae) with phylogenetic consideration. (1st November 2016) - Wei, Hongqing; Ma, Hongyu; Ma, Chunyan; Zhang, Heng; Zhang, Fengying; Wang, Wei; Chen, Wei; Meng, Yongyong; Cheng, Jiahua; Li, Shengfa; Jiang, Yazhou; Ma, Lingbo
Abstract: Here we first isolated and characterized the complete mitochondrial genome DNA of Taenioides anguillaris . It was 16 974 bp in length, and contained 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and a putative control region. The structure and the gene arrangement of this genome were identical to those isolated from other Gobiidae fishes. Twenty-eight genes were encoded by heavy strand, while nine genes were encoded by light strand. The total nucleotide composition of this genome was 28.7% for A, 15.6% for G, 28.6% for C, and 27.1% for T, with a high A + T content of 55.8%. From the neighbor-joining (NJ) phylogenetic tree, we can find that T. anguillaris was genetically closest to species Odontamblyopus rubicundus among 20 species within suborder Gobioidei. This work should be helpful for the studies on population genetic diversity and molecular evolution in T. anguillaris and related fish species.